2020
DOI: 10.1186/s12909-020-1943-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of medical professionalism: preliminary results of a qualitative study

Abstract: Background: The importance of medical professionalism has been well documented in the literature. Cultural background affects the constituents of professionalism. However, few studies have explored the domains of medical professionalism in an Asian context. We aim to describe the views and experiences of both patients and faculty on medical professionalism in an urban Asian city state. Methods: Data for this qualitative study were collected through focus group discussions (FGDs) with patients and in-depth inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 29 publications
2
22
0
1
Order By: Relevance
“…In our study, 4 items "solicited feedback", "advocated on behalf of a patient", "extended his/herself to meet patient needs" and "used health resources appropriately" did not achieve the level of agreement to be included for both rounds, suggesting that these items may be less relevant in the local context as compared to other items in the list. This is largely in congruent with the findings of our previous qualitative study which showed that these items were less relevant to patients and/or faculty [28]. Similarly, in a study to define professionalism in anaesthesiology, "resourcefulness" which is similar to "used health resources appropriately", was deemed to be less important [37].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In our study, 4 items "solicited feedback", "advocated on behalf of a patient", "extended his/herself to meet patient needs" and "used health resources appropriately" did not achieve the level of agreement to be included for both rounds, suggesting that these items may be less relevant in the local context as compared to other items in the list. This is largely in congruent with the findings of our previous qualitative study which showed that these items were less relevant to patients and/or faculty [28]. Similarly, in a study to define professionalism in anaesthesiology, "resourcefulness" which is similar to "used health resources appropriately", was deemed to be less important [37].…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, in a study to define professionalism in anaesthesiology, "resourcefulness" which is similar to "used health resources appropriately", was deemed to be less important [37]. This may be because of the difficulty to agree as to what is "appropriate use of health resources", as raised by participants in this Delphi survey and in our previous qualitative study [28]. Modifications to these items may be needed in the future after the pilot testing of the P-MEX.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Axial coding explores and establishes various relationships between concepts and categories through the coding paradigms of conditions, strategies, and results. Selective coding further deletes and integrates the previous research results, formulates story lines, and constructs a theoretical framework [27][28][29]. For example, when "emphasis on teaching quality" was mentioned extensively by the participants, it was selected as one open code, thus positioning it as a central category of the indicators.…”
Section: Discussionmentioning
confidence: 99%